2011
DOI: 10.1016/j.ijid.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of endocarditis due to Proteus species: a literature review

Abstract: Endocarditis due to Proteus species is very rare. We report a case of endocarditis due to Proteus mirabilis that was successfully treated with ampicillin and gentamicin, and review the treatment regimens of previously published cases of Proteus endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Subsequently, an increasing incidence of IE due to GNB and a changing pattern of risk factors were described among patients with health care contacts (4,5). Most of the knowledge about this clinical entity derived from some case series, single-center experiences, and the ICE study, including 49 patients with IE due to non-HACEK GNB (1,4,(13)(14)(15)(16)(17). Thus, our investigation represents the largest contemporary cohort of patients with IE due to non-HACEK GNB for which data have been collected to date.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, an increasing incidence of IE due to GNB and a changing pattern of risk factors were described among patients with health care contacts (4,5). Most of the knowledge about this clinical entity derived from some case series, single-center experiences, and the ICE study, including 49 patients with IE due to non-HACEK GNB (1,4,(13)(14)(15)(16)(17). Thus, our investigation represents the largest contemporary cohort of patients with IE due to non-HACEK GNB for which data have been collected to date.…”
Section: Discussionmentioning
confidence: 99%
“…KALRA et al (2011) reviewed endocarditis due to Proteus species and OKIMOTO et al (2010) reported P. mirabilis pneumonia. Brain abscesses during P. vulgaris bacteremia were described by BLOCH et al (2010).…”
Section: Pathogenicitymentioning
confidence: 99%
“…The first instance of survival without a surgical intervention was reported in 2007 in a patient treated with ceftriaxone for 4 weeks 7. More recently, a successful outcome was reported with ampicillin and gentamicin for an ampicillin-sensitive strain of P. mirabilis 8. In this instance, echocardiography was prompted after a murmur was detected on examination.…”
Section: Discussionmentioning
confidence: 93%